The dynamics of phosphorus extractability, adsorption, and desorption rates as influenced by phosphorus applications and incubation times - Claassens, A.S. (Andries Stephanus), 1943- (University of Pretoria, 2013)
Thesis (DPhil (Plant Production: Horticulture))--University of Pretoria, 2006.